Long-COVID neurological symptoms are associated with D-dimer levels in COVID-19 patients - Diah Kurnia Mirawati; Pepi Budianto; Rivan Danuaji; Subandi Subandi; Ira Ristinawati; Hanindia Riani Prabaningtyas (Universa Medicina, 2022)
Background Coronavirus disease 2019 (COVID-19) is a disease designated as a global pandemic by the WHO that can manifest clinically as neurological disorders that can occur in the acute phase or after the acute phase (long COVID-19), such as headache, myalgia, anosmia, and cognitive impairment. These neurological disorders as symptoms of long COVID-19 are presumably caused by hypercoagulable conditions characterized by an increase in D-dimer level. This study aims to determine the correlation of long COVID-19 neurological symptoms with hypercoagulable conditions and the role of D-dimer as a biomarker of long COVID-19 neurological symptoms. MethodsThis was a cross-sectional study involving 31 patients with long COVID-19 symptoms. Admitted long COVID-19 cases with recorded D-dimer levels and definitive outcomes were included consecutively. Long COVID-19 neurological symptoms were collected. D-dimer level was measured using immunofluorescence assay and reported in fibrinogen equivalent units (ìg/mL). The correlation between D-dimer levels and neurological clinical manifestations was assessed by using ordinal regression analysis. The p-value of <0.05 was considered statistically significant. ResultsThe mean age of the subjects was 38.81 ± 11.58 years and 18 (58.06%) were female. Long COVID neurological symptoms comprised myalgia, anosmia and cephalgia, and most subjects complained of myalgia (80.65%). On multivariable analysis, long-COVID-19 neurological symptoms were significantly correlated with D-dimer [odds ratio (OR) = 1.05; p=0.020]. ConclusionThe number of neurological long COVID symptoms were significantly correlated with level of D-Dimer. Ultimately, more clarity is needed on the neurological impact of COVID-19, its diagnosis, and its treatment.